Irregular Migration on the Central Mediterranean: A Critical Analysis - Agyare, Patrick (Technium Social Sciences Journal, 2021)
This paper examines the human rights situation of irregular migrants on the Central Mediterranean. For this, it investigates the content and nature of the challenges involved in this migratory phenomenon. The studies conducted on this theme led to the existence of political, legal, and institutional challenges related to the protection of fundamental rights of irregular migrants who undertake unsafe crossing of the Mediterranean to the EU. In this context, it seemed useful to question the capacity of existing norms to grasp the nuances of a constantly changing reality that puts pressure on individuals, states, and international organizations set up to protect them. It further highlights worrying trends of shipwrecks, with over one thousand deaths recorded in the first seven months of 2021, a number that could well underestimate the true number of fatal accidents. At the same time, the security of Europe’s Southern Borders must be respected in the face of unauthorized crossing of the Mediterranean. However, the obstacle to the rescue activities of NGOs, as well as decisions that delay the disembarkation of migrants rescued at sea, does not guarantee the minimum reverence for fundamental rights. This paper aims, therefore, to highlight the dangers inherent in unsafe practices of trafficking or transport of irregular migrants by sea. It further draws attention to both state and non-state actors to respect the fundamental rights of irregular migrants and to save lives at sea. Conversely, the fragmentation of international instruments amid the absence of a sovereign enforcing body can be seen as a limitation constraining the effectiveness of the fundamental rights of the migrants.